Buried road : a novel - Tallo, Katie (Harper, 2024)
When the love of her life disappeared on a camping trip, Gus Monet was devastated. Her daughter was only nine at the time, but young Bly still remembers the heartbreak vividly. Howard had been like a father to her. He was a journalist working on a story that took a dark and dangerous turn. The last time they saw him, he was going to meet a source he believed could blow the story wide open. Three years later, shocked to see Howard's obituary in the paper, Gus and Bly are drawn back to Prince Edward County where he was last seen and where the camper Howard was driving has been found. Sneaking into the camper, mother and daughter find what investigators missed. Hidden behind a secret panel are Howard's notebook, cell phone, and a video message recorded right before he vanished, evidence that turns the cold case red hot. Searching for answers, Gus and Bly vow to follow the story Howard was pursuing and to expose whoever went to deadly lengths to stop him from revealing the truth.